2019
DOI: 10.1002/osp4.373
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to physical activity during and after a behavioural weight loss programme

Abstract: Summary Background Most adults with overweight/obesity participating in behavioural weight loss (BWL) programmes never achieve prescribed physical activity (PA) levels. This study examined changes in PA barriers, their relationships with accelerometer‐measured PA during and after a 12‐month BWL programme, and associations between PA barriers and participant characteristics. Methods Adults (N = 283) in a BWL programme completed the Barriers to Being Active Quiz, a 21‐item self‐report measure that assesses seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Barriers for PA for women have been extensively studied in the context of only cross-sectional studies or qualitative studies. 44 Thus, our results add new insights to the literature. This study has several strengths.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Barriers for PA for women have been extensively studied in the context of only cross-sectional studies or qualitative studies. 44 Thus, our results add new insights to the literature. This study has several strengths.…”
Section: Discussionsupporting
confidence: 60%
“…The intervention in this RCT included personalized strategies to overcome participants' barriers during the brief in-person counseling and via the study app. Barriers for PA for women have been extensively studied in the context of only cross-sectional studies or qualitative studies 44 . Thus, our results add new insights to the literature.…”
Section: Discussionmentioning
confidence: 61%
“…In total, 42 studies measured PA. Seventeen used objective measurement, 37,39,41-43,45,47,55-59,61,68-71 23 measured self-reported PA, 5,16,38,40,44,46,[48][49][50][52][53][54]60,[62][63][64][65][66][67][72][73][74][75][76] and two measured both. 37,42 Accelerometers were used in 11 studies, 37,[41][42][43]45,47,56,57,59,61,71 activity monitors in five, 39,55,58,69,70 and one study employed pedometry. 68 MVPA (weekly minutes) was the most common device measured PA category (n = 12) followed by step count and (n = 4) and total daily PA (n = 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…PA barriers (e.g., stress, time, willpower, fatigue) have consistently been shown to be important indicators of exercise participation as they have been negatively associated with PA outside of 19,20 and within BWL. 21,22 Depressive symptoms, such as low self-worth, fatigue, irregular sleep patterns, sadness, and hopelessness, 23 may make goaldirected behavior change seem more challenging or obstacle-ridden thereby influencing perceived or experienced barriers to PA.…”
Section: Introductionmentioning
confidence: 99%
“…Research is also needed to determine if the perception of PA barriers differs according to level of depressive symptoms. PA barriers (e.g., stress, time, willpower, fatigue) have consistently been shown to be important indicators of exercise participation as they have been negatively associated with PA outside of 19,20 and within BWL 21,22 . Depressive symptoms, such as low self‐worth, fatigue, irregular sleep patterns, sadness, and hopelessness, 23 may make goal‐directed behavior change seem more challenging or obstacle‐ridden thereby influencing perceived or experienced barriers to PA. Research has shown that those with more severe rates of depressive symptoms, most likely indicative of MDD, commonly express barriers to PA related to interest and internal experiences such as motivation, tiredness, and mood, 24 but data from samples with subclinical symptomatology is needed.…”
Section: Introductionmentioning
confidence: 99%